Soul on fire [videorecording (DVD)] - Poirier, Gregory; Courtney, Joel, 1996-; Corbett, John, 1961-; Szostak, Stephanie; McLain, Masey; McCracken, James (Actor); Franklin, DeVon; Macy, William H., 1950-; Amos, Dorothy; Isham, Mark; Hayes, Bob (Cinematographer); O'Leary, John, 1977- (Sony Pictures Home Entertainment, 2025)
"O'Leary's story begins with his miraculous recovery from a near-death accident when he was 9 years old. Give no chance of survival, John endures an unbelievable road to recovery with the support of his family, faith, community and the kindness of his all-time idol, Baseball Hall of Fame announcer Jack Buck. Grateful for his miracle and shaped by life's struggles, John's mission to better the world inspires millions to do the extraordinary."--